Déconstruction et bioconception des bateaux de plaisance : de nouveaux paradigmes pour l’industrie nautique française - Nicolas Bernard (Développement Durable et Territoires)
For half a century, from the 1960s to the 2010s, the French nautical industry has produced hundreds of thousands of pleasure boats, most of them in composite materials, for the national and international markets. Yet it had so far failed to take into consideration the question of the boats’ end of life and the fate of the resulting waste. For the past ten years or so, however, the nautical industry has expressed its desire to adopt the precepts of sustainable development, and has struggled to take into account the issue of pleasure boat breaking and recycling. Some companies in this sector are even taking a pioneering approach by designing units in bio-materials, while the principle of eco-navigation is developing on the coasts of France, which is reflected in many eco-responsible practices. This development is not without an impact on the organization of the nautical sector and on the territories which it concerns.